”Jeg sidder i toget” – Rumlighed i forandring - Larsen, Svend Erik (Slagmark - Tidsskrift for idéhistorie, 2018)
The article asks the question whether the term ‘spatial turn’ implies the same reference to a fundamental paradigmatic shift as Kant’s Copernican revolution or the ‘linguistic turn.’ The answer is no. The article considers the topical interest in spatiality as a more loose recontextualization of basic notions of time and space of a long standing, more in line with a gradual change of meaning from antiquity to the present than with a conceptual revolution